Hakikat Media Pembelajaran di Kelas Tinggi - Parapat, Khoiriah Marta; Daffa, Muhammad Falih; Siregar, Nita Afriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In order to create an efficient and effective level of implementation of learning activities, one of the efforts that must be done is to reduce even if necessary eliminate the verbal information delivery system. The use of media in the teaching and learning process, educators need to be careful in carrying out the selection and determination of the media to be used. Accuracy and accuracy in choosing media will support the effectiveness of the learning process carried out. This study This research uses the literature study method to obtain data, concepts and information related to research variables. The results show that learning media have several characteristics, functions and benefits as well as the principles of choosing learning media in high classes. Therefore, the media is also the main intermediary in bridging learning with learning centers and resources. Media is often the main reliance in conventional learning processes, learning strategies Directly centered on a teacher, this becomes a source of resources and at the same time a center in learning in high grades.